Fruit quality and production of Vitis vinifera L. Chardonnay affected by partial defoliation in tropical highlands (2015)
Using a completely randomized design with twotreatments (50% defoliation and a control without defoliation)and six replications per treatment, the fruit quality and productionof grape plants subjected to early partial-defoliation in Villa deLeyva – Colombia were determined. Five-year-old Vitis vinifera L.'Chardonnay' plants were used as the plant material, planted in atrellis system with distances of 2.1 x 1 m. The plants were partiallydefoliated biweekly, removing every other recently emerged leaf ineach of the plants subjected to the defoliation treatment. 130 daysafter the start of the pruning, the number of harvested clusterswas determined for each of the evaluated plants along with thenumber of berries per cluster, the fresh weight of the clusters,the average berry weight, the fruit pH and diameter, the TSS, theTTA and the fruit maturity index (MI). The average weights of theclusters and the berries were significantly higher in the plantssubjected to a reduced foliar area. All of the fruit quality parametervalues increased with defoliation with the exception of TTA, whichwas higher in the control plants. Therefore, it was concluded thatpartial-defoliation had a pronounced influence on the fruit qualityand production of the 'Chardonnay' grapes.